BO‘LAJAK O‘QITUVCHILARNING AXBOROT KOMPETENTSIYASINI SHAKLLANTIRISH - Nurmaxanov, K.E. (SCIENCE and SOCIETY, 2024)
Informational competence determines the quality of students’ knowledge and skills whish are the result of the learning process; it is one of the most important components of the teacher’s professional components. The author of the article defines such notions as the competence, teacher’s professional competence and informational competence, singles out levels and stages of forming informational competence, analyses the specificity of training students to create and use electronic educational-and-methodological complex in the learning process.